1999
DOI: 10.1038/23716
|View full text |Cite
|
Sign up to set email alerts
|

Notch signalling controls pancreatic cell differentiation

Abstract: The pancreas contains both exocrine and endocrine cells, but the molecular mechanisms controlling the differentiation of these cell types are largely unknown. Despite their endodermal origin, pancreatic endocrine cells share several molecular characteristics with neurons, and, like neurons in the central nervous system, differentiating endocrine cells in the pancreas appear in a scattered fashion within a field of progenitor cells. This indicates that they may be generated by lateral specification through Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
1,054
5
12

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,080 publications
(1,130 citation statements)
references
References 28 publications
59
1,054
5
12
Order By: Relevance
“…Disruption of Notch signalling or its downstream mediators, including HES1, causes widespread expression of Ngn3 in the murine pancreas and accelerated endocrine differentiation [38,39]. Following FOXO1 silencing, a significant decrease in HES1 gene expression and protein abundance was observed in the human fetal islets.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of Notch signalling or its downstream mediators, including HES1, causes widespread expression of Ngn3 in the murine pancreas and accelerated endocrine differentiation [38,39]. Following FOXO1 silencing, a significant decrease in HES1 gene expression and protein abundance was observed in the human fetal islets.…”
Section: Discussionmentioning
confidence: 99%
“…These include Notch1-4, Deltalike 1 (Dll1), Dll3, Jagged1, Jagged2, Serrate1, and Serrate2 (Lammert et al, 2000;Jensen et al, 2000b). Mice deficient for various Notch pathway components, such as RBPJ, Dll1, and Hes1, display pancreatic hypoplasia resulting from precocious endocrine differentiation that causes progenitor pool depletion (Apelqvist et al, 1999;Jensen et al, 2000b;Fujikura et al, 2006). Furthermore, overexpressing Notch3 ICD , which represses Notch1-mediated upregulation of Hes1 in vivo, also results in reduced pancreas size and epithelial branching, with concurrent accelerated endocrine differentiation (Apelqvist et al, 1999).…”
Section: Notch Signaling In Early Pancreatic Progenitor Developmentmentioning
confidence: 99%
“…Mice deficient for various Notch pathway components, such as RBPJ, Dll1, and Hes1, display pancreatic hypoplasia resulting from precocious endocrine differentiation that causes progenitor pool depletion (Apelqvist et al, 1999;Jensen et al, 2000b;Fujikura et al, 2006). Furthermore, overexpressing Notch3 ICD , which represses Notch1-mediated upregulation of Hes1 in vivo, also results in reduced pancreas size and epithelial branching, with concurrent accelerated endocrine differentiation (Apelqvist et al, 1999). Conversely, mice expressing a constitutively active Notch1 Intracellular Domain (N1ICD) over the Pdx1 þ endoderm have greatly impaired endocrine and exocrine differentiation, and the hypoplastic pancreatic epithelium is effectively trapped in the undifferentiated state appropriate to when the NICD expression is activated (Hald et al, 2003;Murtaugh et al, 2003).…”
Section: Notch Signaling In Early Pancreatic Progenitor Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic conversion from biliary to pancreatic development in the Hes1 mutant mice prompted us to examine the expression of Hes1 and Neurog3 (encoding neurogenin 3) in the developing biliary system to see whether the pancreatic differentiation program [5][6][7][8] operates ectopically in the mutant. In situ hybridization showed that Hes1 was expressed in the epithelial cells of the extrahepatic biliary system throughout normal cholangiogenesis (Fig.…”
mentioning
confidence: 99%